Character Education Values in the Animated Series Nussa: A Semiotic Approach - Wahyuni, Syarli; Ahmad Jamin; Daflizar, Daflizar (Institut Agama Islam Negeri Kerinci, Indonesia, 2024)
This study addresses the concern over children’s increasing exposure to YouTube content that often lacks values of character education and may contribute to a crisis of character. Animated films, however, can be an alternative medium for instilling positive values, yet children frequently regard them only as entertainment and overlook their educational aspects. To explore this potential, the animated series Nussa, available on YouTube, was chosen as the research object because it integrates Islamic values and conveys moral lessons in an engaging way. The study employs a descriptive qualitative design within the framework of library research using a structuralism approach. Data were collected through documentation and analyzed using Roland Barthes’ semiotic theory, while validity was ensured through prolonged observation, persistence, and triangulation. Findings reveal three key points: first, nine character values were identified across five episodes of Nussa, namely religiosity, honesty, tolerance, creativity, curiosity, nationalism, friendliness/communicativeness, environmental care, and responsibility; second, denotative meanings illustrated everyday Muslim life through characters like Nussa, Rara, Uma, and Abdul, while connotative meanings emphasized moral values, and mythological meanings reinforced Islamic perspectives on these values; third, methods of transmitting character values included qudwah (role modeling), targhib (motivation), commands, prohibitions, tarhib (warnings), dialogue, and debate. Overall, the study concludes that the Nussa animated series serves not only as entertainment but also as a valuable medium for character education, contributing positively to children’s moral and social development.